Power system stability enhancement through the optimal, passivity-based, placement of svcs - Spanias, Chrysovalantis; Aristidou, Petros; Michaelides, Michalis P.; Lestas, Ioannis (My University, 2018)
Over the last decades, several techniques have been proposed for the optimal placement of FACTS devices across power systems. Although these techniques were shown to improve power system operation, they are usually computationally intractable while having serious inherent limitations. In this paper, we present a novel approach to guide the SVC location identification in order to enhance power system stability. Specifically, the proposed method exploits findings in passivity-based control analysis and design in order to address the most vulnerable-in terms of passivity-buses of the system and consequently the optimal locations for SVC installation. We then show how the incorporation of SVCs at the aforementioned buses can passivate the system and provide guarantees for increased stability. Furthermore, we provide a brief discussion regarding the sizing and the number of required SVC devices in order to guarantee such stability improvement. Finally, we illustrate our results with simulations on the IEEE 68 bus system and show that both the dynamic response and the damping of the system are significantly improved.
Keywords: Optimal placement; Passivity; Power system stability enhancement; Static Var Compensator (SVC)